Transient Delivery of A-C/EBP Protein Perturbs Differentiation of 3T3-L1 Cells and Induces Preadipocyte Marker Genes - Sharma, Nishtha; Kaur, Raminder; Yadav, Binduma; Shah, Koushik; Pandey, Harshita; Choudhary, Diksha; Jain, Prateek; Aggarwal, Aanchal; Vinson, Charles; Rishi, Vikas (Frontiers in Molecular Biosciences, 2021)
Transformation of committed 3T3-L1 preadipocytes to lipid-laden adipocytes involves timely appearance of numerous transcription factors (TFs), foremost among them C/EBPβ, is expressed during early phases of differentiation. Here we describe liposome-mediated protein transfection approach to rapidly downregulate C/EBPβbyA-C/EBP protein inhibitor.SignalsfromEGFP-tagged A-C/EBP protein were observed in 3T3-L1 cells within 2hrs of transfections whereas for A-C/EBP gene transfections equivalent signals appeared in 48hrs. Following transient transfections, expression profiles of 24 marker genes belonging to pro-and anti-adipogenic, cell cycle, and preadipocytes pathways were analyzed. Expectedly, mRNA and protein expression profiles of adipocyte-marker genes showed lower expression in both A-C/EBP protein and gene transfected samples. Interestingly, for preadipocytes and cell fate determinant genes, striking differences were observed between A-C/EBP protein and A-C/EBP gene transfected samples. Preadipocyte differentiation factors Stat5a and Creb were downregulated in A-C/EBP protein samples. Five preadipocyte markers, namely, Pdgfrα, Pdgfrβ, Ly6A, CD34, Itgb1 showed high expression in A-C/EBP protein samples whereas only Ly6A and CD34 were expressed in A-C/EBP gene transfected samples. Pdgfrα and Pdgfrβ, two known cell fate markers were expressed in A-C/EBP protein transfected samples suggesting a possible reversal of differentiation. Our study provides evidences for the immediate and efficient knockdown of C/EBP protein to understand time-dependent preadipocytes differentiation.